Gaya Bahasa Lirik Lagu Band Betrayer Album The Best Of - Rinaldi, Rio; Tamsin, Andria Catri; Zulfadhli, Zulfadhli (Universitas Negeri Padang, 2012)
The purpose of this study were (1) describe the style of the language contained in the lyrics of the song the band's best album of Betrayer, (2) describe the function of a style that is contained in the lyrics of the song the band's best album of Betrayer, (3) describes a style that is dominant contained in the lyrics of the song the band's best album of Betrayer. The data of this study was fifty-four of style from all the lyrics in inventory and in previous analyzes. Source of research data is text or song lyrics band Betrayer, as many as nine songs featured in the best of album. Data were collected using the methods refer to and record as advanced techniques. The findings of the study is a style that is contained in the lyrics of the song with the band Betrayer style as much as 54 languages ​​from around the lyrics of the song in the analysis. Function of language in the style of songs that the band Betrayer, asserted, make poetic, concretize, and smoothing. Style that is dominant in the lyrics of the band Betrayer again the best of this album is the personification, hyperbole, irony, and repetition (anaphora).